Can variation in input explain variation in typical spoken target-language features during study abroad?. Issue 1 (12th December 2022) - Thomas, Anita; Mitchell, Rosamond
Many studies have confirmed the belief that a stay abroad (SA) is beneficial for second language (L2) development. However, substantial variation in learning outcomes has long been acknowledged. Research has identified a range of factors that explain variability in target-language development. However, few studies have focused on the linguistic characteristics of the overall L2 input available to SA participants. In this study, we examine the role of the input situation during SA, in explaining variation in typical spoken language features. We will present six case studies from the longitudinal LANGSNAP corpus of French L2 learners at a university in the United Kingdom, who undertook a two-semester SA in France. For each participant, we established an input profile based on data from questionnaires and interviews collected before, during and following SA. The analysis of learner production over time examined three typical French spoken-language phenomena: The negative particle ne, the pronoun on as a first-person-plural subject and discourse markers. Since these phenomena are variable in both formal and informal French, we compared the learners' production to variation found in three different reference corpora. Overall, results show a convincing relationship between the ongoing input situation and the production of typical spoken language features. Analyses of the reference corpora show differences in the proportions of the studied phenomena according to the level of formality of language use. For the L2 learners, limited engagement in everyday and informal interaction in French corresponds to a weaker use of the phenomena.